2017
DOI: 10.1002/ehf2.12158
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between skeletal muscle mass and cardiac function during exercise in community‐dwelling older adults

Abstract: AimsThis study aimed to investigate the relationship between skeletal muscle mass and cardiac functional parameters in older adults during cardiopulmonary exercise testing (CPET).Methods and resultsSixty‐three Japanese community‐dwelling older adults were enrolled (20 men and 43 women; mean age 80 years, range 65–97 years). Cardiac functional parameters during exercise were assessed using CPET. Skeletal muscle mass index (SMI) was calculated by dividing the appendicular lean mass (measured using dual‐energy X‐… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
16
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 29 publications
3
16
0
Order By: Relevance
“…Similarly, our study showed that peak VO 2 /HR, which is also known as the index of stroke volume (SV) [11], is bi-directionally related to SMI [15]. Therefore, it seems reasonable that HGS would show a bi-directional relationship to the index of CO (=SV x HR) during exercise in this study.…”
Section: Discussionsupporting
confidence: 54%
“…Similarly, our study showed that peak VO 2 /HR, which is also known as the index of stroke volume (SV) [11], is bi-directionally related to SMI [15]. Therefore, it seems reasonable that HGS would show a bi-directional relationship to the index of CO (=SV x HR) during exercise in this study.…”
Section: Discussionsupporting
confidence: 54%
“…Some studies have shown that decreased muscle mass and strength can influence function in several medical conditions. In community dwelling older adults, lower SMI was associated with cardiopulmonary functions [20]. In addition, there was a positive correlation between SMI and peak oxygen uptake [20].…”
Section: Discussionmentioning
confidence: 93%
“…In community dwelling older adults, lower SMI was associated with cardiopulmonary functions [20]. In addition, there was a positive correlation between SMI and peak oxygen uptake [20]. Another study has reported that the elderly with sarcopenia is over three times more likely to fall than non-sarcopenic individuals regardless of age, gender, or other confounding factors [21].…”
Section: Discussionmentioning
confidence: 97%
“…Recently, a high prevalence of cognitive impairment was reported in patients with chronic HF (both HF with reduced and preserved EF). Interestingly, we found that peak VO 2 /HR is related to skeletal muscle mass index, which is an important factor in sarcopenia, and hypothesized that the decline of peak VO 2 /HR with decreased skeletal muscle mass in sarcopenia is a phenotype of HF with preserved EF . Therefore, multiple linear regression analysis to predict MoCA‐J score (cognitive impairment) showed that peak VO 2 /HR is a determinant factor after adjusting for potential confounders (including sarcopenia) among the community‐dwelling people with preserved EF (without HF).…”
Section: Discussionmentioning
confidence: 88%